ENVIRONMENTAL EXTREMISM AS A NEW CHALLENGE OF ECONOMIC SECURITY OF INDUSTRIAL ORGANIZATIONS IN RUSSIA - A. Savin (Вестник университета, 2019)
The article deals with a relatively new phenomenon for the Russian social - ecological extremism. We studied the origins of the protest movement, which lie in the struggle for improving the state of the ecological environment. Illustrative examples describing the consequences of actions of extremists. Displaying a destabilizing effect on the operation of industrial companies participating demarches. The measures to neutralize the environmental extremists.